Self-assembly to function: design, synthesis and broad spectrum antimicrobial properties of short hybrid E-vinylogous lipopeptides - Shankar, S. Shiva; Benke, Sushil N.; Nagendra, Narem; Srivastava, Prabhakar Lal; Thulasiram, Hirekodathakallu V.; Gopi, Hosahudya N. (Journal of Medicinal Chemistry, 2013)
Nonribosomal E-vinylogous gamma-amino acids are widely present in many peptide natural products and have been exploited as inhibitors for serine and cysteine proteases. Here, we are reporting the broad spectrum antimicrobial properties and self-assembled nanostructures of various hybrid lipopeptides composed of 1:1 alternating alpha-and E-vinylogous residues. Analysis of the results revealed that self-assembled nanostructures also play a significant role in the antimicrobial and hemolytic activities. In contrast to the alpha-peptide counterparts, vinylogous hybrid peptides displayed excellent antimicrobial properties against various bacterial and fungal strains. Peptides that adopted nanofiber structures displayed less hemolytic activity, while peptides that adopted nanoneedle structures displayed the highest hemolytic activity.

Functional characterization of novel sesquiterpene synthases from Indian sandalwood, santalum album - Srivastava, Prabhakar Lal; Daramwar, Pankaj P.; Krithika, Ramakrishnan; Pandreka, Avinash; Shankar, S. Shiva; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Indian Sandalwood, Santalum album L. is highly valued for its fragrant heartwood oil and is dominated by a blend of sesquiterpenes. Sesquiterpenes are formed through cyclization of farnesyl diphosphate (FPP), catalyzed by metal dependent terpene cyclases. This report describes the cloning and functional characterization of five genes, which encode two sesquisabinene synthases (SaSQS1, SaSQS2), bisabolene synthase (SaBS), santalene synthase (SaSS) and farnesyl diphosphate synthase (SaFDS) using the transcriptome sequencing of S. album. Using Illumina next generation sequencing, 33.32 million high quality raw reads were generated, which were assembled into 84,094 unigenes with an average length of 494.17 bp. Based on the transcriptome sequencing, five sesquiterpene synthases SaFDS, SaSQS1, SaSQS2, SaBS and SaSS involved in the biosynthesis of FPP, sesquisabinene, beta-bisabolene and santalenes, respectively, were cloned and functionally characterized. Novel sesquiterpene synthases (SaSQS1 and SaSQS2) were characterized as isoforms of sesquisabinene synthase with varying kinetic parameters and expression levels. Furthermore, the feasibility of microbial production of sesquisabinene from both the unigenes, SaSQS1 and SaSQS2 in non-optimized bacterial cell for the preparative scale production of sesquisabinene has been demonstrated. These results may pave the way for in vivo production of sandalwood sesquiterpenes in genetically tractable heterologous systems.

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus

Mechanistic insights on anserine hydrolyzing activities of human carnosinases - Pandya, Vaibhav Kumar; Shankar, S. Shiva; Rajesh, S.; Rathore, Rajeshwari; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (Biochemica ET Biophysica Acta- General Subjects, 2023)
Anserine and carnosine represent histidine-containing dipeptides that exert a pluripotent protective effect on human physiology. Anserine is known to protect against oxidative stress in diabetes and cardiovascular diseases. Human carnosinases (CN1 and CN2) are dipeptidases involved in the homeostasis of carnosine. In poikilothermic vertebrates, the anserinase enzyme is responsible for hydrolyzing anserine. However, there is no specific anserine hydrolyzing enzyme present in humans. In this study, we have systematically investigated the anserine hydrolyzing activity of human CN1 and CN2. A targeted multiple reaction monitoring (MRM) based approach was employed for studying the enzyme kinetics of CN1 and CN2 using carnosine and anserine as substrates. Surprisingly, both CN1 and CN2 can hydrolyze anserine effectively. The observed catalytic turnover rate (Vmax/[E]t) was 21.6 s-1 and 2.8 s-1 for CN1 and CN2, respectively. CN1 is almost eight-fold more efficient in hydrolyzing anserine compared to CN2, which is comparable to the efficiency of the carnosine hydrolyzing activity of CN2. The Michaelis constant (Km) value for CN1 (1.96 mM) is almost three-fold lower compared to CN2 (6.33 mM), representing higher substrate affinity for anserine-CN1 interactions. Molecular docking studies showed that anserine binds at the catalytic site of the carnosinases with an affinity similar to carnosine. Overall, the present study elucidated the inherent promiscuity of human carnosinases in hydrolyzing anserine using a sensitive LCMS/MS approach.
Keywords: Anserine; Carnosinase; Carnosine; Diabetes; LC-MS; MS; Multiple reaction monitoring (MRM); Promiscuity

De novo structure prediction of meteorin and meteorin-like protein for identification of domains, functional receptor binding regions, and their high-risk missense variants - Shankar, S. Shiva; Banarjee, Reema; Jathar, Swaraj M.; Rajesh, S.; Ramasamy, Sureshkumar; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2024)
Meteorin (Metrn) and Meteorin-like (Metrnl) are homologous secreted proteins involved in neural development and metabolic regulation. In this study, we have performed de novo structure prediction and analysis of both Metrn and Metrnl using Alphafold2 (AF2) and RoseTTAfold (RF). Based on the domain and structural homology analysis of the predicted structures, we have identified that these proteins are composed of two functional domains, a CUB domain and an NTR domain, connected by a hinge/loop region. We have identified the receptor binding regions of Metrn and Metrnl using the machine-learning tools ScanNet and Masif. These were further validated by docking Metrnl with its reported KIT receptor, thus establishing the role of each domain in the receptor interaction. Also, we have studied the effect of non-synonymous SNPs on the structure and function of these proteins using an array of bioinformatics tools and selected 16 missense variants in Metrn and 10 in Metrnl that can affect the protein stability. This is the first study to comprehensively characterize the functional domains of Metrn and Metrnl at their structural level and identify the functional domains, and protein binding regions. This study also highlights the interaction mechanism of the KIT receptor and Metrnl. The predicted deleterious SNPs will allow further understanding of the role of these variants in modulating the plasma levels of these proteins in disease conditions such as diabetes.
Keywords: domains; Meteorin; meteorin-like; missense variants; protein-protein interactions; structure prediction

Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry